ANATOMI KONFLIK SOSIAL DI JAWA TENGAH: Studi Kasus Konflik Penistaan Agama di Temanggung - FITRIYAH, DKK, FITRIYAH, DKK (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
bstractSARA (Indonesian acronym of suku/tribe, agama/religion, ras/race andantargolongan/intergroup) conflict is always happened due to the community diversity in Indonesia.Understanding SARA conflict using tool of analysis is important to investigate and propose solution inorder to maintain harmony. Using case study of religious insult in Temanggung, Central JavaProvince, this research analyzes the conflict using DFID framework in order to determine structure,actors, and dynamics of the conflict that is important for conflict resolution.Keywords: conflict, religious insult, structure, actors, dynamics.